1982
DOI: 10.1111/j.1365-246x.1982.tb02798.x
|View full text |Cite
|
Sign up to set email alerts
|

A teleseismic study of the West African craton margin in Senegal: P-wave slowness and azimuth anomalies

Abstract: Slowness-azimuth anomalies for P-arrivals at the Kedougou temporary teleseismic array on the West African craton, near its western margin, are small except for westerly azimuths, implying uniform structure beneath the array itself and the existence of a steeply dipping refracting interface in the mantle to the west. At the Missira array, located on the Mauritanide orogenic belt west of the craton margin, the pattern of slowness anomalies can be explained by north-dipping upper crustal structure, plus a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Hearty et al [ 1977] and Berteussen [ 1976] investigated crustal and upper mantle velocity heterogeneities that are responsible for slowness and azimuth anomalies recorded at seismic array. Briden et al [1982] modeled array slowness and azimuth anomalies to constrain an upper mantle velocity transition zone. Menke et al [1990] noticed the consistent response of threecomponent particle polarization to regional velocity heterogeneities, Lerner-Lam and Park [1989] observed threecomponent polarization anomalies of surface waves across Pacific Ocean, and Walck and Minster [1982] and Powell and Mitchell [this issue] used large amount of polarization vectors to systematically study upper mantle structure beneath southern California.…”
Section: Introductionmentioning
confidence: 99%
“…Hearty et al [ 1977] and Berteussen [ 1976] investigated crustal and upper mantle velocity heterogeneities that are responsible for slowness and azimuth anomalies recorded at seismic array. Briden et al [1982] modeled array slowness and azimuth anomalies to constrain an upper mantle velocity transition zone. Menke et al [1990] noticed the consistent response of threecomponent particle polarization to regional velocity heterogeneities, Lerner-Lam and Park [1989] observed threecomponent polarization anomalies of surface waves across Pacific Ocean, and Walck and Minster [1982] and Powell and Mitchell [this issue] used large amount of polarization vectors to systematically study upper mantle structure beneath southern California.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attributed such systematic errors to lateral velocity variations in the deep mantle (Weichert 1972;Davies and Sheppard 1972;Kanasewich et al 1972Kanasewich et al , 1973Sengupta and Julian 1974;Powell 1975). Conversely, others have attributed the observed anomalies to lateral velocity variations in the crust and upper mantle (Hearty et al 1977;Briden et al 1982;Walck and Minster 1982;Granet 1986;Dainty and Battis 1989). Other research has indicated that such large systematic errors are due to crustal effects beneath recording sites (Niazi and Anderson 1965;Niazi 1966;Sheppard 1967;Chinnery and Toksoz 1967;Cleary et al 1968;Greenfield and Sheppard 1969;Wright et al 1974;Lin and Roecker 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Velocity structure has been investigated through modeling of P-wave ray direction data in a number of regions (Niazi, 1966;Briden et al, 1982;Walck and Minster, 1982;and Steck and Prothero, 1994). Recently, significant advances in the use of P-wave slowness and azimuth data have occurred, via the development of linearized inversion methods (Hu et al, 1994 et al (1953) first introduced a simple algorithm for simulating annealing (that is, the cooling of a melt) using the statistical mechanics framework, and the basic principles of that algorithm are used in most annealing optimization schemes.…”
Section: Introductionmentioning
confidence: 99%